2021
DOI: 10.1371/journal.pone.0253613
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of procoagulant factors in patients with small cell lung cancer

Abstract: Small cell lung cancer (SCLC) patients have augmented risk of developing venous thromboembolism, but the mechanisms triggering this burden on the coagulation system remain to be understood. Recently, cell-derived microparticles carrying procoagulant phospholipids (PPL) and tissue factor (TF) in their membrane have attracted attention as possible contributors to the thrombogenic processes in cancers. The aims of this study were to assess the coagulation activity of platelet-poor plasma from 38 SCLC patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Plasma proteins of circulating MVs and exosomes were characterized and confirmed as previously described [ 26 ] and in accordance with the Minimal Information for Studies of Extracellular Vesicles (MISEV) criteria [ 27 ]. Due to analytical troubleshooting, only 23 of the 24 SCLC samples could be used to investigate exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma proteins of circulating MVs and exosomes were characterized and confirmed as previously described [ 26 ] and in accordance with the Minimal Information for Studies of Extracellular Vesicles (MISEV) criteria [ 27 ]. Due to analytical troubleshooting, only 23 of the 24 SCLC samples could be used to investigate exosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with SCLC are more susceptible to thrombogenic events, and coagulation factors have previously been associated with SCLC 23,48 . High levels of pretreatment D‐dimer or fibrinogen have been linked to inferior survival outcomes 49–51 and poorer response to chemotherapy 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SCLC are more susceptible to thrombogenic events, and coagulation factors have previously been associated with SCLC. 23 , 48 High levels of pretreatment D‐dimer or fibrinogen have been linked to inferior survival outcomes 49 , 50 , 51 and poorer response to chemotherapy. 51 , 52 In the current study, we included two blood coagulation markers: the PRO‐FIB marker, which reflects the thrombin‐mediated degradation of fibrinogen to fibrin, and vWF‐N, which reflects the formation of vWF.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value of tumor TF expression or its plasma level on VTE occurrence and prognosis in LC patients is controversial [ [28] , [29] , [30] , [31] , [32] , [33] , [34] ], possibly because of the method used to detect TF. Some studies evaluated the presence of TF (protein or RNA levels) in tumor tissues [ 28 , 29 ], and others assessed the presence of TF-exposing EVs in blood by flow cytometry or immunocapture, but the specificity of the antibody against TF was sometimes questionable [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antigenic determination of TF is not predictive of its activity, and it has been shown that LC chemotherapy could increase its procoagulant activity via protein disulfide isomerase-dependent TF decryption [ 36 ]. Lastly, there are few prospective studies evaluating TF in LC [ [28] , [29] , [31] , [32] , [33] , 37 ].…”
Section: Introductionmentioning
confidence: 99%